Estimates of genetic variability and correlation studies for some quality traits in cabbage (Brassica oleracea var. capitata ) - MEENA, M L; RAM, R B; LATA, RUBEE; SHARMA, S R (The Indian Journal of Agricultural Sciences, 2012)
The genetic variability, inter-relationship and path analysis for quality traits were studied in 30 diverse cabbage genotypes. A wide range of variation was observed for all most all traits. C 10 recorded the maximum amount of sulphur, carotenoids, ascorbic acid, iron, potassium, zinc, calcium and dry matter. Phenotypic coefficient of variation and genotypic coefficient of variation were highest for ascorbic acid and lowest for potassium and calcium. High heritability estimates were observed for all the quality characteristics, except for zinc and dry matter percent. Ascorbic acid and sulphur content, high genetic advance as percentage of mean coupled with high heritability and low genetic advance as percentage of mean indicated non additive gene action for expression of calcium and potassium. The genotypic correlation coefficient higher than the corresponding phenotypic correlation coefficient for all the parameters. The dry matter had significant and positive correlation with all quality traits. Thus, these traits may effectively be used as a selection criterion for screening potential genotypes in a breeding programme.